MODEL OF SOCIAL AND PSYCHOLOGICAL PREVENTION OF TEENAGERS’ DEVIANT BEHAVIOR - Zhumagaliyeva, Bibinur; Barabanova, Elena (European Scientific Journal, ESJ, 2014)
The searches for solution to overcome the problems of prevention and deviant behavior in teenagers have focused our attention on the concept of personality-oriented approach in learner - centered education. In the psycho-pedagogical science it is established to be quite clear criteria that reveal the essence of deviant behavior of juveniles (teacher isolation, maladjusted, delinquency, instability of values, psychological aggression, social passivity, increased anxiety, conflictprone). The study of the etiology of deviant behavior allows the scientists to isolate the multiplicity of factors that produce such behavior. Causes of deviant behavior of teenagers is a pedagogical isolation, indocileness, tortfeasor, instability of value orientations, psychological aggression, social passivity, increased anxiety, conflict potential.